Pharmacological and Clinical Studies of Medicinal Plants That Inhibit Dipeptidyl Peptidase-IV - Rohani; Febrina E; Wahyuni IS; Levita J (Dove Medical Press, 2023)
Rohani,1,* Ellin Febrina,2,* Indah Suasani Wahyuni,3,* Jutti Levita2,* 1Master Program in Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia; 2Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia; 3Department of Oral Medicine, Faculty of Dentistry, Padjadjaran University, Sumedang, Indonesia*These authors contributed equally to this workCorrespondence: Jutti Levita, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Jl. Raya Bandung-Sumedang km 21, Sumedang, 45363, Indonesia, Tel +6222-84288888 Ext 3510, Email jutti.levita@unpad.ac.idAbstract: Dipeptidyl peptidase IV (DPP-IV) is an enzyme responsible for the degradation of the incretin hormone glucagon-like peptide-1 (GLP-1). DPP-IV plays a significant role in regulating blood glucose levels by modulating the activity of GLP-1. In the context of diabetes, DPP-IV inhibitors effectively block the activity of DPP-IV, hence mitigating the degradation of GLP-1. This, in turn, leads to an extension of GLP-1's duration of action, prolongs gastric emptying, enhances insulin sensitivity, and ultimately results in the reduction of blood glucose levels. Nonetheless, reported adverse events of DPP-IV inhibitors on T2DM patients make it essential to understand the activity and mechanism of these drugs, particularly viewed from the perspective of finding the effective and safe add-on medicinal plants, to be implemented in clinical practice. This review is intended to bring forth a thorough overview of plants that work by reducing DPP-IV activity, from computational technique, enzymatic study, animal experiments, and studies in humans. The articles were searched on PubMed using "Plants", "DPP-IV", "DPP-IV inhibitor", "GLP-1", "Type 2 diabetes", "diabetes", "in silico", "in vitro", "in vivo", "studies in human", "clinical study" as the query words, and filtered for ten years of publication period. Eighteen plants showed inhibition against DPP-IV as proven by in silico, in vitro, and in vivo studies; however, only ten plants were reported for efficacy in clinical studies. Several plant-based DPP-IV inhibitors, eg, Allium sativum, Morus Alba, Curcuma longa, Pterocarpus marsupium, and Taraxacum officinale, have established their functional role in inhibiting DPP-IV and have proven their effectiveness through studies in humans earning them a prominent place in therapeutic discovery.Keywords: antidiabetics, antioxidants, diabetes mellitus, incretin hormone, medicinal plants